2015 IEEE Global Communications Conference (GLOBECOM) 2014
DOI: 10.1109/glocom.2014.7417726
|View full text |Cite
|
Sign up to set email alerts
|

Outage Analysis of Spectrum Sharing Energy Harvesting Cognitive Relays in Nakagami-m Channels

Abstract: Energy harvesting (EH) cognitive relays are an exciting solution to the problem of inefficient use of spectrum while achieving green communications and spatial diversity. In a spectrum sharing scenario, we investigate the performance of a cognitive relay network, where a secondary source communicates with its destination over Nakagami-m channels via decode-and-forward EH relays while maintaining the outage probability of the primary user below a predefined threshold. Specifically, we derive a closed-form expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Similarly, in cognitive radio, using energy harvesting for energy-limited relays, SUs can achieve significant performance gains [21], [22]. In [22], under spectrum sharing with a PU, an EH relay which forwards the secondary data is considered, while a tradeoff between primary interference constraint and energy constraint due to EH nature of relays is investigated in [23].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in cognitive radio, using energy harvesting for energy-limited relays, SUs can achieve significant performance gains [21], [22]. In [22], under spectrum sharing with a PU, an EH relay which forwards the secondary data is considered, while a tradeoff between primary interference constraint and energy constraint due to EH nature of relays is investigated in [23].…”
Section: Introductionmentioning
confidence: 99%
“…In cognitive radio, using energy harvesting for energylimited relays, authors in [25]- [27] showed that SUs could achieve substantial performance gains without battery recharging or replacement. In [25], authors investigated a trade-off between the primary interference constraint and the energy constraint due to EH nature of relays and found the region of dominance for each of the constraints. The EH model considered in [25] was a generic one and did not assume any specific source of energy.…”
Section: Related Workmentioning
confidence: 99%
“…In [25], authors investigated a trade-off between the primary interference constraint and the energy constraint due to EH nature of relays and found the region of dominance for each of the constraints. The EH model considered in [25] was a generic one and did not assume any specific source of energy. In [26], authors considered the RF EH model for secondary relays, where relays harvested energy from ST's information signals using a time switching policy.…”
Section: Related Workmentioning
confidence: 99%
“…Outage performance in a SWIPT-enabled CCRN under a Nakagami fading channel is analyzed in [9] considering decode-and-forward (DF) relaying. The authors in [10] and [11] investigate the performance of a similar SWIPT-enabled CR network in underlay mode.…”
Section: Introductionmentioning
confidence: 99%